Somewhere east of life - Aldiss, Brian Wilson 1925-2017 (Carroll & Graf, 1994)
The 21st century has given birth to a new racket, memory pirates. The novel follows the protagonist, Roy Burnell, an architect, as he tries to recover ten years of stolen architectural knowledge and sexual experiences, the latter chopped up and sold on the black market to lovers of soft porn. By the author of A Tupolev Too Far.
Keywords: Architectural historians -- Fiction; Memory disorders -- Fiction; Men -- Sexual behavior -- Fiction; Black humor (Literature); Science fiction